FRI0475 ANTI-CD74 antibodies as diagnostic biomarker for early axial spondyloarthritis: data from the spondyloarthritis caught early (SPACE) cohort study. (15th June 2017) - Winter, JJ de; Sande, MG van de; Baerlecken, N; Berg, IJ; Ramonda, R; Heijde, D van der; Gaalen, FA van; Witte, T; Baeten, DL
Abstract : Background: Diagnosis of axSpA is often delayed with 5–10 years. A robust biological disease marker is lacking and could decrease the current diagnostic delay. Two studies showed that serum anti-CD74 IgG antibodies are increased in SpA 1, 2 . Objectives: To explore the value of anti-CD74 antibodies as diagnostic biomarker for axSpA in patients with early, chronic back pain. Methods: We tested the prevalence of anti-CD74 IgG and IgA antibodies in patients from the SPondyloArthritis Caught Early (SPACE) cohort by enzyme-linked immunosorbent assay (ELISA). Patients from the SPACE cohort have chronic back pain for >3 months and ≤2 years with an onset <45 years. Results: We included 560 patients of the SPACE cohort, of whom 274 patients were diagnosed with axSpA by a rheumatologist at baseline. Anti-CD74 IgG levels did not differ between patients with and without axSpA (p=0.152, Table 1 ). Median anti-CD74 IgA levels (tested with either casein or BSA as a blocking buffer) were higher in patients with axSpA (both p<0.0001). Despite these differences at the group level, the diagnostic value of the anti-CD74 IgA antibodies was limited as shown by ROC analysis. The optimal cut off according to ROC analysis was an optical density (OD) of 0.875, providing a sensitivity of 38.3% and a specificity of 77.6%. In line with previous reports, further analysis revealed that total IgA levels were elevated in early axSpA patients vs. non-SpA early back pain patients (p=0.008). When correcting the level of anti-CD74 IgA for the level of total IgA, the differentiating capacity of anti-CD74 disappeared for casein but remained intact for BSA (casein: p=0.731, BSA: p=0.038). Additional analyses using the ASAS classification criteria rather than a clinical diagnosis of axSpA, a strict combination of clinical diagnosis and ASAS classification criteria (excluding patients fulfilling the ASAS axSpA criteria without a clinical diagnosis and vice versa) (Table 1 ) and using the clinical diagnosis at 1 year of follow-up yielded similar results. Conclusions: Serum anti-CD74 IgA antibody levels, but not serum anti-CD74 IgG levels, are elevated in patients with axSpA versus non-SpA with back pain of <2 years duration. However, ROC analyses revealed that these numerical differences are of limited diagnostic value in these patients with early back pain. References: Baraliakos, X. et al. High prevalence of anti-CD74 antibodies specific for the HLA class II-associated invariant chain peptide (CLIP) in patients with axial spondyloarthritis. Ann. Rheum. Dis. 1–5 (2013). Baerlecken, N. T. et al. Autoantibodies against CD74 in spondyloarthritis. Ann. Rheum. Dis. 73, 1211–4 (2014). Disclosure of Interest: J. de Winter: None declared, M. van de Sande Grant/research support from: Novartis, Eli Lilly, Boehringer Ingelheim, Benecke, Takeda, Tillotts, MSD, Cellgene, N. Baerlecken: None declared, I. Berg: None declared, R. Ramonda: None declared, D. van der Heijde: None declared, F. van Gaalen: None declared, T. Witte: None declared, D. Baeten Grant/research support from: Pfizer, MSD, AbbVie, UCB, Novartis, Janssen, Boehringer Ingelheim., Consultant for: Pfizer, MSD, AbbVie, UCB, Novartis, Janssen, Boehringer Ingelheim, Eli Lilly, Roche, BMS, Glenmark, Employee of: UCB